2014
DOI: 10.1080/08870446.2014.951651
|View full text |Cite
|
Sign up to set email alerts
|

Self-care activities and glycated haemoglobin in Iranian patients with type 2 diabetes: Can coping styles and social support have a buffering role?

Abstract: Findings indicate that health care providers, within the context of the Iranian social and cultural situation, should pay more attention to psychosocial factors when addressing self-care activities. Delineation of the role of coping styles and social support might be useful for identifying patients in need of particular counselling and support for improving self-care activities and HbA1c levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 38 publications
3
22
1
1
Order By: Relevance
“…Norberg deemed that low emotional support could increase the risk of T2DM in women (Norberg et al 2007). On the contrary, self-care, effective coping styles, and social support were negatively correlated with HbA1c (Shayeghian et al 2015). In this study, the SEM indicated that coping resources have positive effects on abnormal glucose metabolism and buffered the negative effects of occupational stressors and personal strain in a way, but there was no statistical significance.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Norberg deemed that low emotional support could increase the risk of T2DM in women (Norberg et al 2007). On the contrary, self-care, effective coping styles, and social support were negatively correlated with HbA1c (Shayeghian et al 2015). In this study, the SEM indicated that coping resources have positive effects on abnormal glucose metabolism and buffered the negative effects of occupational stressors and personal strain in a way, but there was no statistical significance.…”
Section: Discussioncontrasting
confidence: 75%
“…Although many studies, such as the Whitehall II study followed by the Japanese male office study (Heraclides et al 2012;Nakanishi et al 2001), demonstrated that stress modulated blood glucose and affected insulin activity that could result in glucose intolerance (de Groot et al 2003;Heden Stahl et al 2014;Norberg et al 2007). Some stressors (poor physical environment, low emotional support, lack of social support) were reported related to T2DM (Kim et al 2015;Norberg et al 2007;Shayeghian et al 2015;Sorensen et al 2013). Other occupational stressors, such as role overload, role conflict, role boundary, and role insufficiency, could affect depressive symptoms (Perry-Jenkins et al 2007;Wang et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, HCPs should familiarise themselves with patients’ treatment goals, diabetes knowledge and blood glucose variations in addition to supporting their engagement in SMBG. Implementing these measures can help patients to feel understood, accepted and relieved and engage in more effective SMBG behaviours (Hojat et al., ; Kim et al., ; Shayeghian et al., ). Moreover, most of our participants acknowledged personal responsibility for their own health and changes in disease conditions and voluntarily performed SMBG as a daily routine.…”
Section: Discussionmentioning
confidence: 99%
“…Although, little information about how the average blood sugar control in the hand of Iranian patients, increasing prevalence of diabetes, sound alarm of poor control of diabetes in Iranians. [ 9 10 ]…”
Section: Introductionmentioning
confidence: 99%